A Study on impact of Pandemic on performance of children Fund - Manisha kumari; Dr. Vishal Kumar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
COVID-19 and the worldwide lockdown left life in worse condition in which people struggle to meet their livelihood. People are concerned about their lives, jobs, savings, education cost and investments. This paper had analysed the changes in the mutual fund industry in India due to the pandemic from 2018 to March 2021. Children fund regular growth funds has been considered for this study to analyse their performance along with the other investment avenue to secure child future. The results show that the return of majority of the funds had jumped, while some funds had return to normal during the period. The paper has analysed solution oriented schemes from the perspective of number of folios, redemption/repurchase, asset under management and return.